Hubungan Antara Kualitas Pribadi Konselor dan Minat Siswa Terhadap Layanan Konseling Perorangan - Ahadiyah, Maulida Fakhrina; awalya, awalya (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
This study aims to determine: (1) an overview of personal qualities counselor, (2) a description of the interest of the students individual counseling services, and (3) the relationship between the counselors personal qualities and interests of students on individual counseling services. The population in this study was a counselor and student at SMK 1 Kedungwuni Kabupaten Pekalongan. Pengumpuan method of data using a personal quality scale counselor and scale of interest. Data were analyzed using descriptive statistics and analysis of product moment correlation. The analysis shows the level of personal qualities counselor in either category, the level of students interest towards individual counseling services in the high category, and there is a positive relationship between the counselors personal qualities and interests of students on individual counseling services.